The peculiarities of preschool child`s space and time perception as a reason of successful learning at school - Nataliia Holota (Vasyl Stefanyk Precarpathian National University, 2017)
In terms of preschool education content renovation, focus of educational process onpersonal development, children preparation for school acquires particular importance.Child`s space and time cognition are vital in the ensuring of above-mentioned process. Spaceand time are the universal, basic categories in children`s cognition of material, natural andsocial environment, successful mastering of different kinds of activities, social adaptationdevelopment. However "space" and "time" are the most complicated categories forunderstanding and perception by preschool children. According to the results of theoreticaland preschool education practice analysis, the peculiarities of young and preschool agechildren`s space and time perception and the significance of their formation for schoolpreparation are considered in the article. Key words: space, time, space and time perception, preschool education, preschoolchild, activity, sensory development, ways of reality cognition.